Investigation of collective variables in inelastic antiproton-proton interaction at 22.4 Gev/c and 32 Gev/c energies - Mamykenov, D.T.; Temiraliev, T. (Recent Contributions to Physics, 2016)
In article, we investigate the collective variables in the antiproton-proton interactions at a momentum of 22.4 GeV/c and 32 GeV/c. The value of the partial inelastic coefficient and sphericity, which describe hadrons jet, are calculated and graphs of their dependence build up for 3 groups in the multiplicity of annihilation and non-annihilation channels. We analyzed graphs, and obtained correlation between sphericity and partial inelastic coefficient. It was determined that the distribution of the partial inelastic coefficients in non-annihilation channel concentrated in area , whereas in the annihilation channel concentrated in area . It is shown that the larger values of sphericity observed at large partial inelastic coefficient, and the maximum of distributions sphericity and the distribution itself are shifted towards higher values of S. Also the distribution of sphericity becomes symmetrical when produced particles number is increasing.